6(2+6b)-8(b+4)=-20

Simple and best practice solution for 6(2+6b)-8(b+4)=-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2+6b)-8(b+4)=-20 equation:


Simplifying
6(2 + 6b) + -8(b + 4) = -20
(2 * 6 + 6b * 6) + -8(b + 4) = -20
(12 + 36b) + -8(b + 4) = -20

Reorder the terms:
12 + 36b + -8(4 + b) = -20
12 + 36b + (4 * -8 + b * -8) = -20
12 + 36b + (-32 + -8b) = -20

Reorder the terms:
12 + -32 + 36b + -8b = -20

Combine like terms: 12 + -32 = -20
-20 + 36b + -8b = -20

Combine like terms: 36b + -8b = 28b
-20 + 28b = -20

Add '20' to each side of the equation.
-20 + 20 + 28b = -20 + 20

Combine like terms: -20 + 20 = 0
0 + 28b = -20 + 20
28b = -20 + 20

Combine like terms: -20 + 20 = 0
28b = 0

Solving
28b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Divide each side by '28'.
b = 0

Simplifying
b = 0

See similar equations:

| 66-8a=2(19-3a) | | (x^2-x)-14(x^2-x)+24=0 | | 2x+7=6x+31 | | y+8=0.5(x-3) | | 3w-12=-27 | | 2a^2=1+a | | (25x^2-100x+50)+(50x-50)(2x)-(20x)(5-5x)-50x^2=0 | | x-8=-3x+11 | | d(t)=(20+3t)t | | 2(2x+8)+4=4x+20 | | Y-1(12-2x)=6 | | 2x^2+7x-32=0 | | X+15=3x-75 | | 65-2c=-23 | | (30-1y)+1y=30 | | -140/21 | | -6x+10y=134 | | (25x^2-100x+50)(50x-50)(2x)-(20x)(-5)(5-5x)(-10x^2)=0 | | 180+7x=360 | | (20-2x)(10-2x)(x)= | | (25x^2-100x+50)(50x-50)(2x)-(20x)(-5)(5-5x)(10x^2)=0 | | 5c+3=29 | | 2x+2(x+6)=12 | | 3x^2-12x^2+36x=0 | | 4s-8=15 | | 2x^2-36x=720 | | 18+8x=88 | | (25x^2-100x+50)(50x-50)(2x)-(-100x)(5-5x)(10x^2)=0 | | 5/7x3/5 | | 5y-20+110+y=180 | | W-4.40=9.60 | | x=30+-1y |

Equations solver categories